STUDI LITERATUR : MANAJEMEN PEMBINAAN JAMAAH HAJI DAN UMRAH MELALUI KEMENTRIAN AGAMA INDONESIA PADA MASA PANDEMI COVID-19 - Meichio Lesmana; Fikriyyatun Nabila; Indra Soleh Husni; Isma Fathya Fajriati (Multazam : Jurnal Manajemen Haji dan Umrah, 2022)
The purpose of this article is to find out how the process of coaching pilgrims and Umrah during the Covid-19 pandemic is carried out by the Ministry of Religion. This research is a literature research where the author relies on various kinds of literature to obtain data and uses a qualitative approach because the data produced is in the form of a description. This research utilizes a similar study or relates to the guidance of hajj and umrah pilgrims during the covid-19 period. The Ministry of Religion provides various coaching programs for Hajj pilgrims in 3 parts of learning, namely online, offline, and blended learning (hybrid) using electronic technology and internet-based technology. Currently, the Ministry of Religion utilizes a number of learning platforms, including Youtube, Twitter, Whatsapp, Telegram, Instagram and Zoom. The implementation of coaching activities is carried out by complying with health protocols, it's just that sometimes the process of coaching activities is hampered and not optimal because it is carried out with an online system. This means that the guidance for Hajj and Umrah pilgrims runs effectively even during the Covid-19 pandemic.